Race, racialization and Indigeneity in Canadian universities. Issue 3 (4th May 2017) - Henry, Frances; Dua, Enakshi; Kobayashi, Audrey; James, Carl; Li, Peter; Ramos, Howard; Smith, Malinda S.
Abstract: This article is based on data from a four-year national study of racialization and Indigeneity at Canadian universities. Its main conclusion is that whether one examines representation in terms of numbers of racialized and Indigenous faculty members and their positioning within the system, their earned income as compared to white faculty, their daily life experiences within the university as workplace, or interactions with colleagues and students, the results are more or less the same. Racialized and Indigenous faculty and the disciplines or areas of their expertise are, on the whole, low in numbers and even lower in terms of power, prestige, and influence within the University.